2008
DOI: 10.4319/lom.2008.6.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidification in multiple stable isotope analyses

Abstract: The effect of in situ acidification on the stable isotope ratios of carbon and nitrogen was tested in several invertebrates living in an eelgrass system. Dried and ground samples of individuals were weighted in silver cups and treated in situ with 10% HCl. Control samples were measured without acidification. This treatment to remove inorganic carbon significantly decreased the δ13C values. The δ15N values were not affected by this method of acidification. In contrast to the acid‐washing method the tested proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 28 publications
(37 reference statements)
2
42
0
1
Order By: Relevance
“…These tests consist in dropping a small amount of sample powder in 10 % HCl. Effervescence indicates presence of carbonates, while the lack of visible bubbling suggests that no significant amount of carbonates is present in the tissues (Jaschinski et al 2008). Here, champagne tests indicated that Schizasteridae caeca did not contain carbonates and did not require acidification.…”
Section: Stable Isotope Analysismentioning
confidence: 74%
“…These tests consist in dropping a small amount of sample powder in 10 % HCl. Effervescence indicates presence of carbonates, while the lack of visible bubbling suggests that no significant amount of carbonates is present in the tissues (Jaschinski et al 2008). Here, champagne tests indicated that Schizasteridae caeca did not contain carbonates and did not require acidification.…”
Section: Stable Isotope Analysismentioning
confidence: 74%
“…However, the elimination of carbonates is absolutely necessary for some organisms, especially small gastropods and crustaceans that could only be sampled by crushing their shell or carapace. Preliminary analyses showed no statistically significant differences of d 15 N in acid or no-acid treatments (Jaschinski et al 2008a).…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…Analytical tools, such as stable carbon and nitrogen isotopes, and fatty acid analysis, may add detail to these generalisations (Desvilettes et al 1997;James et al 2000b;Jones and Waldron 2003;Hadwen and Bunn 2005;Jaschinski et al 2008a). The fractionation of d 13 C is thought to be low-maximally 1% per trophic level-and d 13 C is therefore useful to identify different carbon sources.…”
Section: Introductionmentioning
confidence: 99%
“…Dried above-ground plant biomass, litter and residues were homogenised and ground into a fine powder using a ball mill. The Champagne test (Jaschinski et al, 2008) was used to determine that no residue samples contained inorganic C. Consequently, acidification of samples was deemed unnecessary. Organic %C, %N and δ 13 C were measured for all samples using an isotope ratio mass spectrometry -elemental analyzer (Thermo Delta V) at the University of Hawaii (HILO).…”
Section: Elemental and Isotopic Analysismentioning
confidence: 99%